2011
DOI: 10.1074/jbc.m110.167239
|View full text |Cite
|
Sign up to set email alerts
|

Rho Kinase II Phosphorylation of the Lipoprotein Receptor LR11/SORLA Alters Amyloid-β Production

Abstract: LR11, also known as SorLA, is a mosaic low-density lipoprotein receptor that exerts multiple influences on Alzheimer disease susceptibility. LR11 interacts with the amyloid-␤ precursor protein (APP) and regulates APP traffic and processing to amyloid-␤ peptide (A␤). The functional domains of LR11 suggest that it can act as a cell surface receptor and as an intracellular sorting receptor for trans-Golgi network to endosome traffic. We show that LR11 over-expressed in HEK293 cells is radiolabeled following incub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 59 publications
3
52
0
1
Order By: Relevance
“…Phosphorylation of SORLA in vivo was described before [16][17][18]. Our phosphorylation analysis further detected phosphorylation of synapsin 1 and 2 at the putative 14-3-3 binding sites (Ser666 and Ser546) in mouse cortex, a prerequisite for 14-3-3 binding to these sites (Fig.…”
Section: Sorla Interacts With Synapsin Via 14-3-3-adaptor Proteinssupporting
confidence: 74%
“…Phosphorylation of SORLA in vivo was described before [16][17][18]. Our phosphorylation analysis further detected phosphorylation of synapsin 1 and 2 at the putative 14-3-3 binding sites (Ser666 and Ser546) in mouse cortex, a prerequisite for 14-3-3 binding to these sites (Fig.…”
Section: Sorla Interacts With Synapsin Via 14-3-3-adaptor Proteinssupporting
confidence: 74%
“…2B). In addition, SORLA is phosphorylated by protein kinase C and ROCK2 (rho-activated coiled-coil kinase 2) (Lane et al, 2010a;Herskowitz et al, 2011), enzymes that have previously been implicated in amyloidogenic processing, because inhibition of the activity of these kinases by knockdown or pharmacological intervention increased the production of Ab (Zhou et al, 2003;Leuchtenberger et al, 2006). Reducing ROCK2 activity impairs the trafficking of SORLA and decreases ectodomain shedding of the receptor .…”
Section: Lrp1mentioning
confidence: 99%
“…Pharmacologic inhibition of ROCKs can induce protein degradation pathways, including autophagy, in mammalian cells (Bauer et al, 2009;Koch et al, 2014). However, whether ROCKs influence tau synthesis or protein homeostasis is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy (macroautophagy) mediates protein aggregate degradation and represents the major cellular pathway for soluble tau disposal in primary neuron cultures (Verhoef et al, 2002;Krüger et al, 2012). Autophagy can be pharmacologically induced with rapamycin through the inhibition of mammalian target of rapamycin (mTOR), and treatment with rapamycin reduced insoluble tau levels in Drosophila models of tauopathy (Berger et al, 2006;Bakhoum et al, 2014). Other studies revealed that mTOR and the mTOR effector p70 S6 kinase (S6K) likely have direct effects on tau synthesis, phosphorylation, and aggregation Tang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation